A Self-Assembling Amphiphilic Peptide Dendrimer-Based Drug Delivery System for Cancer Therapy - Dandan Zhu; Huanle Zhang; Yuanzheng Huang; Baoping Lian; Chi Ma; Lili Han; Yu Chen; Shengmei Wu; Ning Li; Wenjie Zhang; Xiaoxuan Liu (MDPI AG, 2021)
Despite being a mainstay of clinical cancer treatment, chemotherapy is limited by its severe side effects and inherent or acquired drug resistance. Nanotechnology-based drug-delivery systems are widely expected to bring new hope for cancer therapy. These systems exploit the ability of nanomaterials to accumulate and deliver anticancer drugs at the tumor site via the enhanced permeability and retention effect. Here, we established a novel drug-delivery nanosystem based on amphiphilic peptide dendrimers (AmPDs) composed of a hydrophobic alkyl chain and a hydrophilic polylysine dendron with different generations (AmPD KK2 and AmPD KK2K4). These AmPDs assembled into nanoassemblies for efficient encapsulation of the anti-cancer drug doxorubicin (DOX). The AmPDs/DOX nanoformulations improved the intracellular uptake and accumulation of DOX in drug-resistant breast cancer cells and increased permeation in 3D multicellular tumor spheroids in comparison with free DOX. Thus, they exerted effective anticancer activity while circumventing drug resistance in 2D and 3D breast cancer models. Interestingly, AmPD KK2 bearing a smaller peptide dendron encapsulated DOX to form more stable nanoparticles than AmPD KK2K4 bearing a larger peptide dendron, resulting in better cellular uptake, penetration, and anti-proliferative activity. This may be because AmPD KK2 maintains a better balance between hydrophobicity and hydrophilicity to achieve optimal self-assembly, thereby facilitating more stable drug encapsulation and efficient drug release. Together, our study provides a promising perspective on the design of the safe and efficient cancer drug-delivery nanosystems based on the self-assembling amphiphilic peptide dendrimer.